Knee function after a mean of 19 years Post-retirement in 65 Italian semi-professional rugby veterans. - Goderecci, Remo; De Dominicis, Simone; Necozione, Stefano; Ciriello, Vincenzo; Angelozzi, Massimo; Calvisi, Vittorio; Logroscino, Giandomenico (Acta Biomedica Atenei Parmensis, 2022)
Background and aim sport activity has been largely correlated to the development of knee osteoarthritis, but only few papers have investigated the long-term impact of a rugby career on the knee joint. The aim of this retrospective study was to evaluate the incidence and epidemiology of knee osteoarthritis and general health in a population of 65 retired semi-professional rugby players.Methods demographic and anamnestic analysis was recorded and Oxford Knee score, SF-12 and VAS were submitted to all veterans in order to assess current knee function, general health condition and level of pain. Parametric analysis of Spearman was used to evaluate the statistical significance on these results and the Kruskal-Wallis test was used to assess the significant differences between the questionnaire results and the demographic and anamnestic records.Results we found that players who sustained a knee injury during their career have a current reduction of the knee function compared to veterans who did not suffer any injury and who showed values comparable with those of the health population. In terms of general and mental health, athletes who retired later have now a better condition than those who retired from the sport  earlier.Conclusions: we concluded that knee injury prevention should be an unequivocal priority because although rugby is a high energy sport, it does not increase the risk of knee osteoarthritis in absence of serious knee injuries.